Literacy Class Program Management at Taman Lentera School Semarang - Aulia Denaya; Imam Shofwan (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2023)
Managing the Literacy Class Program at Taman Lentera School in Semarang is an urgent priority to enhance students' reading, writing, and critical thinking skills, which will directly impact the improvement of education quality and empowerment of the younger generation in the future. This study aims to reveal the implementation of the literacy class program at Taman Lentera School related to management, supporting, and inhibiting factors. The design used in this study is qualitative, using a case study approach. The subjects of the study are founders, alumni volunteers, and active volunteers. Data were collected through (1) observation, (2) interviews, and (3) documentation. The data validity technique used in this study is source and technique triangulation, with data analysis using data collection, reduction, presentation, and drawing conclusions. The results revealed that program management includes six functions: (a) planning, (b) organizing, (c) mobilizing, (d) coaching, (e) assessment, and (f) development. Volunteers, community leaders, youth, parents, and children are supporting factors. Meanwhile, the inhibiting factors are consistency, communication, and coordination of volunteers, which are still lacking, limited literature owned by Taman Lentera School, and the Covid-19 pandemic.